Масштабування мережі оптико-електронних станцій із застосуванням технології LoRa - Шостко, І. С.; Шлома, О. К.; Майба, М. А.; Дробяз, М. О. (ХНУРЕ, 2022)
An analysis of the possibility of scaling a network consisting of optoelectronic stations was carried out. For communication these stations use Ebyte E32 modules that support LoRa technology. The abstracts discuss the main characteristics of the Ebyte E32 modules, network requirements and topology. Scaling calculations were carried out for two types of devices - the command node and the end node. The structure of each node was also considered. Based on the obtained results and calculations, options for scaling and creating clusters of optical systems were presented.
Keywords: технології безпроводового зв’язку; технології LoRa; оптико-електронні станції